Construct a porous carbon structure 3D-NOPC doped with N and O as the sulfur main body for durable lithium-sulfur batteries. (10th February 2023) - Wang, Xin; Guo, Baiyu; Liu, Lei; Zhang, Fengyu; Xia, Chuangui; Cui, Lishan; Yang, Feng
Abstract: Lithium-sulfur (Li-S) batteries have consistently demonstrated high specific energy capacity and density, making them one of the most promising lithium-ion battery successors. However, the shuttle effect of polysulfide intermediates and the low conductivity of S/Li2 S, greatly confine the Li-S battery applications. Herein, we utilized a one-step carbonization technique for synthesizing nitrogen (N) and oxygen (O) double-doped three-dimensional porous carbon (3D-NOPC) to overcome these difficulties. One-step carbonization of sodium citrate combined with polyvinyl pyrrolidone (PVP) yields 3D nanoporous carbonaceous frameworks which achieve porosity for sulfur species accommodation and confinement effect simultaneously. The porous carbon structure of the 3D-NOPC host owns a huge surface area (490 m 2  g −1 ) and pore volume (0.385 cm 3  g −1 ) as well as a high N, O doping concentration (2.8 and 5.3 at%). The 3D-NOPC@S cathode delivers a reversible capacity of around 900 mAh g −1 at 0.5 C and a maintained capacity of 703 mAh g −1 after 200 cycles, in virtue of the confinement effect, polysulfides adsorption, and conductivity enhancement. The initial cyclic discharge specific capacity of the 3D-NOPC@S cathode is 617 mAh g −1 at 2 C rate, with a reversible capacity of 543 mAh g −1 after 500 cycles and superb cycling stability with an ultralow decay rate of 0.024% per cycle. This research uses hierarchical porous materials engineering to limit shuttle polysulfide moieties in sulfur host materials for efficient and stable Li-S batteries.